The liver X receptor agonist TO901317 protects mice against cisplatin-induced kidney injury. (December 2015) - Yang, Meng; Wang, Rong; Sun, Jing; Yu, Kezhou; Chen, Bing; Xu, Liang; Zhao, Bing; Wang, Haiping
Liver X receptors are in the nuclear receptor superfamily and are contained in the regulation of lipid and cholesterol metabolism. Besides, liver X receptors are considered crucial regulators of the inflammatory response and innate immunity. The current study evaluates the in vivo effects that the synthetic liver X receptor agonist TO901317 protects against cisplatin-induced kidney injury in mice. Mice received cisplatin administration through a single intraperitoneal injection (20 mg/kg in saline). And then the mice were treated with the TO901317 by daily gavage (10 mg/kg/day) 12 h postcisplatin administration, and cisplatin nephrotoxicity was evaluated. At 72 h after cisplatin treatment, elevated plasma urea and creatinine levels ( P  < 0.05) were evidenced which indicates the renal dysfunction of the vehicle-treated mice, consistent with tubular necrosis, protein cast, dilation of renal tubules, and desquamation of epithelial cells in renal tubules. In contrast, the severity of renal dysfunction and histological damage was reduced in TO901317 treated mice ( P  < 0.05). In accordance, circulating tumor necrosis factor alpha levels, renal tumor necrosis factor alpha, p47 phox, gp91 phox, and protein expression levels and COX-2 mRNA, renal monocyte chemoattractant protein 1, VACAM-1 mRNA and intercellular adhesion molecule-1 contents, and renal prostaglandin E2 amounts, were higher in samples from cisplatin-treated mice in comparison with controls ( P  < 0.05) but attenuated in the TO901317 treatment group ( P  < 0.05). Taken together, treatment with the liver X receptor agonist TO901317 ameliorated the inflammatory response and oxidative stress in cisplatin-induced kidney injury in mice.